Out of School Children in Nigeria: Causes, Social Implications and Way Forward - Niyi Jacob Ogunode; Chinwuba Mary Adanna; Victor Olugbenga Ayoko (International Journal on Integrated Education, 2022)
This paper examined the concept of out-of-school children in Nigeria, the factors responsible for out-of-school children, the social implications of out-of-school children and suggested way forward. Secondary data were used in the paper. The data were sourced from print and online publications. The paper identified causes of out-of-school children in Nigeria to include; poor funding of education, corruption, poor implementation of the Child Rights Act, insecurity problems, lack of political will to address the problems, high rate of poverty, and high fertility rate. The paper also concluded that the social implications of out-of-school children include security challenges, shortage of skilled manpower in future, bad international image, high levels of illiteracy and high socio-economic and dependency issues. The paper recommended among other things that the federal, state and local governments should come up with programmes to address the problem of out-of-school children in Nigeria. Also, adequate funding should be allocated to the education sector at all levels of government.